Haloaurate and halopalladate imidazolium salts: structures, properties, and use as precursors for catalytic metal nanoparticles. - Serpell, C; Cookson, J; Thompson, A; Brown, C; Beer, P (2013)
The synthesis and characterisation of a series of new gold- and palladium-containing symmetrical imidazolium salts are described which display significant cation-dependent effects determined by the structure of the alkyl chains of the imidazolium motifs. Whereas direct reduction of the Pd salts can produce stable nanoparticles (NPs) coated by imidazolium salts, the addition of strong base to the Pd or Au salts before reduction gives stable NPs, potentially pacified by N-heterocyclic carbene units. The possibility of NP surface protection by metal-carbon bonds in these systems is investigated by spectroscopic, synthetic, and catalytic investigations, providing support for the hypothesis. Significantly, the catalytic activity of the NPs is not inhibited by the continued presence of the ligands.